HASIL BELAJAR IPS TERPADU MODEL PBL DAN DL DENGAN MEMPERHATIKAN KEMAMPUAN AWAL - Meilani Meilani; Tedi Rusman; Nurdin Nurdin (FKIP Unila, 2015)
This research aimed to determine the effectiveness of the PBL and DL model in improving learning result in Integrated Social Science by paying attention to students' prior knowledge. The method used is the quasi experimental method. Based on the results of the research, it obtained (1) There is a difference of learning result in Integrated Social Science between the model of PBL and DL, (2) Results of Integrated Social Science learning using PBL model is higher than the DL at students who have a high initial ability, (3) Results of Integrated Social Science learning using PBL model is lower than the DL at students who have a low initial ability, (4) There is an interaction between learning model with the initial ability of students to learn the results of the Integrated Social Science, (5) There is a difference of learning result in Integrated Social Science between the students' initial ability of high and low, and (6) PBL model is more effective than DL in Integrated Social Science learning.Penelitian ini bertujuan untuk mengetahui efektivitas antara model PBL dan DL dalam meningkatkan hasil belajar IPS Terpadu dengan memperhatikan kemampuan awal siswa. Metode yang digunakan adalah metode eksperimen semu. Berdasarkan hasil penelitian diperoleh (1) Ada perbedaan hasil belajar IPS Terpadu antara model PBL dan DL, (2) Hasil belajar IPS Terpadu menggunakan model PBL lebih tinggi dibandingkan DL pada siswa yang memiliki kemampuan awal tinggi, (3) Hasil belajar IPS Terpadu menggunakan model PBL lebih rendah dibandingkan DL pada siswa yang memiliki kemampuan awal rendah, (4) Ada interaksi antara model pembelajaran dengan kemampuan awal siswa terhadap hasil belajar IPS Terpadu, (5) Ada perbedaan hasil belajar IPS Terpadu antara siswa kemampuan awal tinggi dan rendah, dan (6) Model PBL lebih efektif dibandingkan DL pada pembelajaran IPS Terpadu.Kata kunci: DL, hasil belajar, kemampuan awal, PBL